Creative remediation of Pynstiller by Fanie Viljoen: From short story to graphic novel - Greyling, S.F. (Literator, 2012)
In the Transgressions and boundaries of the page project, artists and writers were invited to create artist’s books and thereby to transcend the possibilities of the codex form of the book. This article discusses one of the projects, namely the creative remediation by Fanie Viljoen of his own short story (word), Pynstiller [‘Painkiller’], which deals with the phenomenon of selfmutilation among teenagers, into a graphic novel (word and image). The creative process and product are investigated according to the concepts of media, narratology, picture book and comic book theory. With reference to the two versions of the text, it is indicated how the narrative and theme of the short story are emphasised or extended in the graphic version, and particularly how access to the experienced world of the first-person narrator has been broadened. It appears that the visual narrative elements and the interaction between word and image together contribute towards the narrative, characterisation, portrayal of the theme and the subsequent effect on the reader-viewer. Finally, Fanie Viljoen’s remediation of Pynstiller confirms the premise that the artist’s book is an ideal medium to challenge and transcend boundaries.